Understanding Access to Justice and Conflict Resolution at the Local Level in the Central African Republic - World Bank Group (Washington, DC, 2013)
The Central African Republic (CAR) is coming out of a long period of political and social turmoil that have left the country weak and with fragile institutions. However, over the last few years the security situation has improved and the state institutions have started to stabilize. In order to improve on these achievements, CAR needs to engage in a long process of strengthening state and community based institutions while ensuring that security is improved to show people a reduction of violence relatively quickly. The 2011 World Development Report (WDR) on conflict, security and development sees the delivery of citizen security as central to achieving resilience and returning to stability. This study aims to better understand how people in CAR experience justice and conflict resolution with the objective of exploring opportunities to strengthen access to justice and conflict resolution mechanisms in the country. The study has carried out a field mapping of how the population is handling issues of justice and conflict resolution at the local level. The authors have also engaged government officials, Non-Government Organizations (NGOs), and local experts in a series of workshop to discuss the findings of the mapping and possible operational directions. Finally, on the request of the government, the study has also included an assessment of how issues of local and customary justice where handled in other African countries with a longer experience in this area.